Amniopatch treatment for preterm premature rupture of membranes before 23 weeks' gestation and factors associated with its success - Ji-Hee Sung; Jin-Yi Kuk; Hyun-Hwa Cha; Suk-Joo Choi; Soo-young Oh; Cheong-Rae Roh; Jong-Hwa Kim (Elsevier, 2017)
Objective: The purpose of this study is to investigate the factors associated with successful amniopatch treatment in patients with iatrogenic preterm premature rupture of membranes (iPPROM) or spontaneous PPROM (sPPROM) before 23 weeks' gestation. Materials and methods: This cohort study included 28 women who received amniopatch treatment due to iPPROM or sPPROM at 15-23 weeks' gestation. Patients' clinical characteristics before performing the amniopatch, factors associated with the procedure, pregnancy and neonatal outcomes were compared between the iPPROM and sPPROM groups, and also between the successful and failed groups. Results: The amniopatch was successful in 6 of 28 patients (21.4%) with a success rate of 36.4% (4/11) and 11.8% (2/17) in the iPPROM group and sPPROM group (P = 0.174), respectively. The success group had a longer PPROM-to-delivery interval, fewer cases of clinical chorioamnionitis, larger birth weight, and lower neonatal intensive care unit admission rate than the failed group. The success rate of amniopatch procedure was proportional to maximal vertical pocket prior to procedure, which showed statistically significant association (adjusted odds ratio: 3.62, 95% confidence interval: 1.16-11.31, P = 0.027). Conclusion: The amniopatch treatment success rate was higher in the iPPROM group than the sPPROM group, but was not statistically significant. The neonatal outcome was more favorable when the amniopatch was successful. However, the only predictive factor associated with successful amniopatch was a larger amniotic fluid volume before the procedure.